H2 content of galaxies inside and around intermediate redshift clusters. Issue Volume 15:Issue S359(2020) (March 2019) - Spérone-Longin, Damien
Abstract: Dense environments have an impact on the star formation rate of galaxies. As stars form from molecular gas, looking at the cold molecular gas content of a galaxy gives useful insights on its efficiency in forming stars. However, most galaxies observed in CO (a proxy for the cold molecular gas content) at intermediate redshifts, are field galaxies. Only a handful of studies focused on cluster galaxies. I present new results on the environment of one medium mass cluster from the EDisCS survey at z ˜ 0.5. 27 star-forming galaxies were selected to evenly sample the range of densities encountered inside and around the cluster. We cover a region extending as far as 8 virial radii from the cluster center. Indeed there is ample evidence that star formation quenching starts already beyond 3 cluster virial radii. I discuss our CO(3-2) ALMA observations, which unveil a large fraction of galaxies with low gas-to-stellar mass ratios.